Mapping small molecule binding sites with phage display technology - Makowski, Lee (Henry Stewart Talks, 2008)
How do you identify the molecular target of a small molecule drug?, Flexible regions are key players, P-loop of ATP-binding proteins is an important example, Can display libraries of flexible peptides on proteins select those that bind to the ligand, Selection is through an affinity process called biopanning, Success depends on the diversity of the library, Diversity depends on how many different peptides are in the library and their relative abundance, RELIC can be used to calculate the diversity of a library from the sequences of ~100 peptides, Identification of motifs from a population is easy if the motif is very strong, Taxol-binding peptides were also identified by phage display and those peptides were used to identify the position on tubulin where taxol is bound and to identify Bcl-2 as a taxolbinding protein, Significant data from a variety of sources argue that the taxol-Bcl-2 interaction is important to the clinical efficacy of taxol
Archived at 2020/08/13